Strategy For Strengthening The Institution Of Mustard Farmers in Torongrejo Village, Junrejo District, Batu City - Mere, Daniel; Gunawan, Cakti Indra; Santosa, Budi (International Research & Development for Human Beings (IRDH), 2025)
The farming institution that has been established in Torongrejo Village has not yet functioned maximally in providing services to its members. However, Torongrejo Village has significant potential for mustard plant development. The objective of this research is to understand the strategies for strengthening the Mustard Farming Institution in Torongrejo Village, Junrejo District, Batu City, as well as to identify the strengths, weaknesses, opportunities, and threats in strengthening the Mustard Farming Institution in Torongrejo Village, Junrejo District, Batu City. This study employs a qualitative method. Data were obtained through interviews, questionnaires, and documentation. The number of respondents involved was 41 farmers from 6 farmer groups. Data were analyzed using SWOT analysis. The results showed that the greatest strength factor in strengthening the mustard farming institution is the availability of Human Resources Training in managing the Mustard Farming Institution. The biggest weakness factor is the limitation of the younger generation interested in vegetable farming. Meanwhile, the greatest opportunity for strengthening the institutional capacity of mustard farmers is the chance to manage farmer institutions professionally with the availability of human resources training. The biggest threat is the government's policy changes regarding the use of agricultural land for vegetables, as well as the declining number of vegetable farmers if there are no young vegetable farmers. The formulation of strategies that can be implemented to strengthen the institutional capacity of mustard farmers in Torongrejo Village, Batu City includes 14 strategies, consisting of 4 strategies in the S-O component, 4 strategies in the W-O component, and 3 strategies each in the S-T and W-T components. The suggestion for the farmers' organization in this research is to pay attention to the strengths, weaknesses, opportunities, and threats that have been identified as evaluation material in the activities program for mustard plant agriculture in Torongrejo Village.